ANALISIS KESALAHAN DALAM TULISAN NARATIF SISWA SMAN 1 LANGOWAN ( Tinjauan Linguistik Terapan ) - B A L O, D E W I S A R T I K A (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research, entitled â€œError Analysis in the narrative composition of the students of SMAN 1 Langowan,â€ is an attempt to identify, classify and analyze the kinds of errors in the narrative composition produced by the students of SMAN 1 Langowan. This research gives contribution in terms of understanding the error analysis especially the errors of the narrative composition. Ellisâ€™s theory was used to analyze the errors in the narrative composition of students of SMAN 1 Langowan. Data were taken from 40 students in XI IPA 5 of SMAN 1 Langowan by asking them to hand write a narrative composition at home in piece of paper about their experience when they were on holiday. The result of this research shows that there are three kinds of errors made by students; they are omission, misinformation and misordering. Errors of omission made by students are omission of to be, omission of the ending for plural nouns, omission of a preposition, omission of auxiliary verbs (to be, to do, to have and modals), omission of an article, and omission conjunction. Errors of misinformation are misinformation of preposition, misinformation of auxiliary verb, misinformation of singular and plural nouns, misinformation of colocation, and misinformation of word spelling. Errors of misordering are misordering of object and misordering of time compliment. Â Key word: error analysis, narrative composition, SMAN 1Langowan